Enhancing pain management knowledge and quality of life in cancer patients through autogenic relaxation - Sukartini, Tintin; Marina, Navy Sealsi Adinda Prisca; Zamroni, Asroful Hulam; Abidah, Aqmarina; Darmawan, Luh Gede Wirani Riskayanti; Serengga, I Made Dwi Budhiasa Ari; Isdaryanti, Lisa; Lestari, Dwi Puji; Nurhidayah, Kiki Fajar; Prakoso, Wisnu Guntur; Fauzi, Achmad; Azhadin, Rizki Nur (Community Empowerment, 2025)
Uncontrolled proliferation of cancer cells is the underlying cause of cancer in patients. This community service aimed to enhance cancer patients' knowledge and understanding of pain management using an autogenic relaxation technique incorporating specific movements and guided suggestions. The method involved demonstrations and health education sessions. This activity was attended by 30 cancer patients aged >18 years undergoing radiotherapy or chemotherapy. The study results indicated a 37.3% improvement in the participants' knowledge and understanding of the provided pain management education, increasing from 50% to 87.3%. The application of autogenic relaxation techniques effectively reduced pain intensity, and patients demonstrated increased independence in performing these techniques. Consequently, the quality of life for cancer patients undergoing treatment can be optimized.